Development of Cutting Force Model of Aluminum Nitride ceramic processed by Micro End Milling - Moola, Mohan Reddy; Gorin, Alexander; Abou-El-Hossein, K. (Trans Tech Publications, 2011)
Advanced ceramics are difficult to do machining due to brittle nature. High cuttingforces will generate in the machining, which will affect the surface integrity of final product.Selection of proper machining parameters is important to obtain less cutting force. The presentwork deals with the study and development of a cutting force prediction model in end millingoperation of Aluminum Nitride ceramic. The cutting force equation developed using ResponseSurface Methodology (RSM) to analyze the effect of Spindle speed, feed rate and axial depth of cut.The cutting tests were carried under dry condition using two flute square end micro grain carbideend mills.